Comparison of refractive development and retinal dopamine in OFF pathway mutant and C57BL/6J wild-type mice - Chakraborty, Ranjay (Molecular Vision, 2014)
PURPOSE: Proper visual transmission depends on the retinal ON and OFF pathways. We used Vsx1−/− mice with a retinal OFF visual pathway defect to determine the role of OFF pathway signaling in refractive development (RD) of the eye. METHODS: Refractive development was measured every 2 weeks in Vsx1−/−, Vsx1+/+ (both on 129S1/Sv background), and commonly used C57BL/6J mice from 4 to 12 weeks of age. Form deprivation (FD) was induced monocularly from 4 weeks of age using head-mounted diffuser goggles. Refractive state, corneal curvature, and ocular biometry were obtained weekly using photorefraction, keratometry, and 1310 nm spectral-domain optical coherence tomography. Retinal dopamine and its metabolite, 3,4-dihydroxyphenylacetate (DOPAC), were measured using high-performance liquid chromatography (HPLC). RESULTS: During normal development, the Vsx1−/− and Vsx1+/+ mice showed similar myopic refractions at younger ages (4 weeks, Vsx1−/−: −5.28±0.75 diopter (D); WT: −4.73±0.98 D) and became significantly hyperopic by 12 weeks of age (Vsx1−/−: 3.28±0.82 D; WT: 5.33±0.81 D). However, the C57BL/6J mice were relatively hyperopic at younger ages (mean refraction at 4 weeks, 3.40±0.43 D), and developed more hyperopic refractions until about 7 weeks of age (8.07±0.55 D) before stabilizing. Eight weeks of FD did not induce a myopic shift in the 129S1/Sv animals (0.16±0.85 D), as opposed to a significant shift of −4.29±0.42 D in the C57BL/6J mice. At 4 weeks of visual development, dopamine turnover (the DOPAC/dopamine ratio) was significantly greater in the 129S1/Sv mice compared to the C57BL/6J mice. FD did not alter the levels of dopamine between the goggled and opposite eyes for any genotype or strain. CONCLUSIONS: OFF pathway signaling may not be critically important for normal refractive development in mice. Elevated retinal dopamine turnover in early refractive development may prevent FD myopia in 129S1/Sv mice compared to C57BL/6J mice.